ChemInform Abstract: Conjugate Umpolung of β, β‐Disubstituted Enals by Dual Catalysis with an N‐Heterocyclic Carbene and a Broensted Acid: Facile Construction of Contiguous Quaternary Stereocenters. Issue 11 (March 2015) - Li, Jun‐Long; Sahoo, Basudev; Daniliuc, Constantin‐G.; Glorius, Frank
Abstract The diastereoselective reaction of isatins with β, β‐disubstituted enals by NHC/Broensted acid dual catalysis is demonstrated to give spirocyclic butyrolactones in good yields and diastereoselectivities.